Sosialisasi Lahan Kampus II Universitas Syiah Kuala di Kecamatan Mesjid Raya, Kabupaten Aceh Besar - Subhan Subhan; Ilyas Ilyas; Mustanir Mustanir; Agussabti Agussabti; Munawar Khalil (Universitas Teuku Umar, 2023)
The purpose of implementing this community service activity is to provide understanding, knowledge and the importance of developing the Syiah Kuala University Campus (USK) as a means of education. The method used is the lecture method, which describes the material that has been prepared, the question and answer method, which is to respond to the level of understanding of the participants' understanding of what has been conveyed and the discussion method, namely the presenter and participants have a dialogue that discusses issues around USK Campus II. While the targets of this activity are community leaders from Neuheun Village, Durung Village, and Ladong Village, Mesjid Raya District, Aceh Besar Regency. The results obtained are expected to build awareness and increase public understanding of the importance of developing Campus II Syiah Kuala University as an educational facility.